(4x+9)=2x+(3x-12)

Simple and best practice solution for (4x+9)=2x+(3x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+9)=2x+(3x-12) equation:


Simplifying
(4x + 9) = 2x + (3x + -12)

Reorder the terms:
(9 + 4x) = 2x + (3x + -12)

Remove parenthesis around (9 + 4x)
9 + 4x = 2x + (3x + -12)

Reorder the terms:
9 + 4x = 2x + (-12 + 3x)

Remove parenthesis around (-12 + 3x)
9 + 4x = 2x + -12 + 3x

Reorder the terms:
9 + 4x = -12 + 2x + 3x

Combine like terms: 2x + 3x = 5x
9 + 4x = -12 + 5x

Solving
9 + 4x = -12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
9 + 4x + -5x = -12 + 5x + -5x

Combine like terms: 4x + -5x = -1x
9 + -1x = -12 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + -1x = -12 + 0
9 + -1x = -12

Add '-9' to each side of the equation.
9 + -9 + -1x = -12 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = -12 + -9
-1x = -12 + -9

Combine like terms: -12 + -9 = -21
-1x = -21

Divide each side by '-1'.
x = 21

Simplifying
x = 21

See similar equations:

| 6+x+2x=27 | | x+5/2-2x+10/9=5 | | Y=x^2+10+17 | | 5t^2=1-5t | | X^2-1=x/4 | | 2.2x+55.4=6.5-14.1x | | 4x^2-63= | | 106=4x-7(-2x+8) | | x^2+16x-25=0 | | 2/7(14x+7/2)-3x=9 | | H^2+11H+30=0 | | H^2+11H-30=0 | | d^2+6=10d-10 | | 2a^2+5a-4=0 | | x^3-47=-20 | | 0.4c=8 | | 20(y^2+1)=4(y+5) | | xcubed-47=-20 | | 6/700 | | 4x^2+9x+12=0 | | -10x+18=-3(5x-7)-8 | | 1/3x-4(2/3x-3)=2/3x-6 | | (4k-5)(7k+7)= | | 7x+12y-9=0 | | -7x-3(-4x+9)=-57 | | -7z-7z=7z+9-9z | | x+2x=64 | | 2f=-27 | | -(8+4n)=-6(3n-1) | | x+3x=8(x-3)+2(x+3) | | 2x+2=1X-5 | | 3y^2-36y+9=0 |

Equations solver categories